THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE PRESERVATION AND RESTORATION OF THE ARCHITECTURAL HERITAGE OF UKRAINE - Balabanov, Igor (Theory and practice of design, 2025)
Traditional methods of restoration of architectural monuments often include physical interventions that may not accurately recreate the original structure of the object, which can lead to the loss of historical integrity. There are many reasons for such distortions, the main ones are traditionally considered to be the following: incorrect analysis of the object, errors in the design part of the reconstruction, errors in the choice of restoration technologies. Purpose. To identify a range of scientific and practical areas focused on the use of artificial intelligence tools to preserve the architectural heritage of Ukraine. Methodology. Based on the developments of the scientific architectural school of the Kharkiv National University of Urban Economics named after O.M. Beketov, artificial intelligence tools in the restoration and preservation of architectural monuments are divided into three main blocks - analysis, modeling and design. For each block, an analysis of the principles of using AI tools was conducted. Results. Over the past decades, artificial intelligence (AI) has become a significant tool in the field of restoration of architectural heritage. Dozens of specialized software products that actively use AI make it possible to simplify and accelerate the analysis of architectural objects, increase the accuracy of their restoration, minimize the risks of the human factor and critical errors. AI transforms traditional restoration methods, offering new opportunities for the analysis, documentation and restoration of historical objects. One of the most transformative innovations in this field has been 3D reconstruction of ancient monuments, which can not only digitally restore complex details of heritage objects, but also provide valuable information about their historical significance. Scientific novelty. In the national scientific tradition, the problems arising in such areas of AI use as data collection, the complexity of the objects under study and the ethical aspects of preserving cultural heritage have not been sufficiently studied. The authors of the study identified and summarized possible prospects for using artificial intelligence in the preservation of architectural heritage. Practical relevance. This research aims to identify and capture the revolutionary potential of AI in heritage conservation, ensuring that cultural and architectural monuments are not only preserved, but can also be restored with previously unattainable accuracy.